Prevalence of Metabolic Syndrome in a Suburban Community of Nepal - Sharma, Deewakar; Baidya, Sajan Gopal; Raut, Roshan; Rajbhandari, Sujeeb; K C, Man Bahadur; Lamichanne, D; Yadav, D; Tuladhar, S; Koirala, Bhagwan (Nepalese Heart Journal, 2017)
In context of rapidly rising prevalence of cardiovascular disease and risk factors in the developing world it has become important to study the scenario in its various aspects. This study conducted between March and July, 2007 in a suburban Nepali population deals with prevalence of metabolic syndrome according to the recently modified criteria for Asians. Altogether 150 subjects were randomly selected. The main component of the survey included administration of predetermined questionnaire, physical examination which included waist circumference measurement, height, weight, blood pressure measurement (twice), 12-lead ECG and fasting blood sample for lipid profile and glucose level. Prevalence of metabolic syndrome in our study according to the recent criteria developed by AHA/NHBLI is 12.4%. Significant Proportion of subjects diagnosed as having metabolic syndrome was not obese by traditional criteria but had increased waist circumference. Elevated triglyceride level was the most common component among subjects with metabolic syndrome was not obese by traditional criteria but had increased waist circumference. Elevated triglyceride level was the most common component among subjects with metabolic syndrome. Prevalence of metabolic syndrome syndrome in a suburban Nepali community seems to be significant. Thus, it is time for the developing countries to realize that the prevention of non-communicable diseases should also receive as much attention as that of nutritional and communicable diseases.